Pathological interactions between the endothelin-1 and the angiotensin- converting enzyme among Tunisian coronary patients. Issue 1 (December 2016) - Chalghoum, Abdelkader; Noichri, Yosri; Dandana, Azza; Baudin, Bruno; Miled, Abdelhédi; Ferchichi, Salima
Abstract Background The correct understanding of the biochemical and metabolic interactions between coronary risk factors contribute to the exploration of cardiovascular pathophysiology and improves therapeutic care. The aim of this study was to explore the endothelin-1 (ET-1) concentration and the angiotensin converting enzyme (ACE) activity among Tunisian patients with coronary heart disease, and to investigate the metabolic relationships between these two markers, … and to assess the possible relationship between them and the different risk factors. In this present study, ET-1 concentration was determined by an analytical method (High Performance Chromatography, coupled by Mass Spectrometry), ACE activity was measured by a kinetic method for patients and healthy controls. These subjects (157 patients and 142 controls) beneficed also by a biochemical exploration (lipid, apolipoproteins and glucose profiles) to quantify cardiovascular risk. Results A statistically significant increase of the ET-1 concentration was found among patients compared to healthy controls (15.2 ± 5.3 nM vs 7.1 ± 2.7 nM, p < 0, 00001). For the ACE activity, in spite the treatment of the majority of patients (97%) with ACE inhibitors, this activity was statistically elevated in patients compared to healthy subjects (86.7 ± 25.4 IU/L vs 42.8 ± 12.1 IU/L, p  < 0.00001). Furthermore, a statistically positive correlation was identified between these two cardiac markers (r  = 0.68p  < 0.00001). Conclusion The study of the metabolic relationship between the ET-1 and ACE among coronary patients reveals other therapeutics targets.